ANALYSIS OF THE COMPATIBILITY OF SPORTS IN THE PROCESS OF PHYSICAL DEVELOPMENT OF CHILDREN WITH THEIR PHYSICAL, FUNCTIONAL AND MENTAL CAPABILITIES - Nurmatov Baxrom Bektemirovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Choosing such a sport, let it corresponds to the physical, functional, and mental capabilities of the child. The start of sports training of children is determined by the state of Health and the general level of development, as well as the physiological description of this or that sport as a result of the effective selection of sports activities, several factors are required to be taken into account. and in this process, the child’s organism develops.